Graphite composite material, preparation method thereof and application of graphite composite material in lithium ion battery
By using solvent hot bonding of amino graphite and carboxylated graphite in graphite materials and composite technology of transition metal doped hard carbon and carbon nanotubes, the problem of poor dynamic performance of existing graphite electrode materials is solved, and higher electronic conductivity and fast charging performance are achieved.
Patent Information
- Application Number
- CN202510094373.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The existing graphite electrode materials have poor dynamic performance, including conductivity, rate performance, etc., which is difficult to meet the needs of lithium-ion batteries to improve fast charging performance.
The solvent hot bonding is carried out with the aid of a coupling agent, and the first carbonization treatment is performed to obtain modified graphite; then the transition metal-doped hard carbon is combined on the surface of the modified graphite, and carbon nanotubes are grown in situ on the hard carbon surface by vapor deposition to form a graphite composite material.
The electronic conductivity and ion transmission channels of graphite electrode materials are significantly improved, the fast charging, stability and other properties of the material are improved, and the detachment rate of lithium ions is improved.
Smart Images

Figure CN119852375A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery electrode materials, and in particular to a graphite composite material and a preparation method thereof and application thereof in lithium ion batteries. Background Art
[0002] As the market's requirements for negative electrode materials with fast-charging performance increase, the negative electrode used in lithium-ion batteries is required to have excellent fast-charging performance. The current commercial negative electrode is mainly composed of graphite and the soft carbon or hard carbon coated on its surface, and undergoes secondary granulation. Due to the large impedance caused by the difference in bonding force between the materials caused by the granulation of the materials, and the poor electronic conductivity of the soft carbon or hard carbon coated on the outer layer, the improvement in fast-charging performance is limited. The current graphite materials have all undergone high-temperature graphitization, and there are no chemical groups on the surface of the material, resulting in deviations in kinetic performance; at the same time, the specific surface area of the current graphite material is relatively low, which affects the kinetic performance of the material.
[0003] In response to the problem of unsatisfactory kinetic properties of graphite materials, there are some improvement schemes in the prior art. For example, Chinese patent No. CN114361410A discloses a fast-charging lithium battery, whose negative electrode sheet includes: a porous copper foil; a slurry layer, which is arranged on both sides of the porous copper foil, and the slurry layer includes a first negative electrode layer, a second negative electrode layer and a third negative electrode layer; the slurry layer coating method is as follows: S1, graphite particles, polyaniline-carbon nanotube particles, a binder, a conductive agent and a solvent are mixed to form a first slurry, and the first slurry is coated on both sides of the porous copper foil and dried and compacted to obtain a first negative electrode layer; S2, graphite-hard carbon particles, a binder, a conductive agent and a solvent are mixed to form a second slurry, and the second slurry is coated on the outside of the first negative electrode layer to form a second negative electrode layer; S3, graphite-hard carbon-carbon nanotube particles, a binder, a conductive agent and a solvent are mixed to obtain a third slurry, and the third slurry is coated on the outside of the second negative electrode layer to obtain a third negative electrode layer.
[0004] For example, a Chinese patent document with publication number CN114447305A discloses a multi-carbon-based fast-charging negative electrode composite material, which has a core-shell structure, with the core being graphite particles doped with nitrogen and tin and a hard carbon composite, and the outer shell being carbon nanotubes and an amorphous carbon composite layer.
[0005] In summary, although there are some improvement methods in the existing technology, the kinetic properties of graphite negative electrode materials, such as conductivity and rate performance, still need to be further improved. Summary of the invention
[0006] The invention provides a graphite composite material and a preparation method thereof and application in a lithium ion battery, thereby solving the problem of poor kinetic performance of graphite electrode materials in the related art.
[0007] The technical solution of the present invention is as follows: The present invention provides a method for preparing a graphite composite material, comprising the following steps: S1, mixing amino graphite, carboxyl graphite, conductive agent, coupling agent and solvent, performing solvent thermal treatment, taking filter residue, drying and carbonizing for the first time to obtain modified graphite; S2, mixing the modified graphite, transition metal precursor and carbon source, drying and carbonizing for a second time to obtain graphite@transition metal doped hard carbon material; S3, in-situ growing carbon nanotubes on the surface of the graphite@transition metal-doped hard carbon material to obtain a graphite composite material.
[0008] As a further technical solution, the mass ratio of the amino graphite, carboxyl graphite, conductive agent and coupling agent is 100:50~150:1~5:1~10.
[0009] As a further technical solution, the mass ratio of the total mass of the amino graphite and the carboxylated graphite to the solvent is 1-3:10.
[0010] As a further technical solution, the mass ratio of the carbon source, the transition metal precursor, and the modified graphite is 10-30:1-5:100.
[0011] As a further technical solution, the solvent includes water and / or an organic solvent, and the organic solvent is a water-soluble organic solvent including one or more of C1-C6 alcohols and acetone.
[0012] As a further technical solution, the preparation method of the amino graphite comprises the following steps: Amine compounds and graphite are used as raw materials for mixed reaction, and the filter residue is subjected to ammoniation and roasting to obtain amino graphite; The amine compound includes a diamine or a polyamine compound, and preferably, the amine compound includes a C2-C8 diamine compound; The mass ratio of the amine compound to graphite is 10-50:100; An organic solvent is also added to the mixed reaction, and the mixed reaction time is 1 to 6 hours at a temperature of 50 to 100° C.; The ammoniating calcination is carried out in an ammonia atmosphere; The time of the ammoniation calcination is 1 to 3 hours.
[0013] As a further technical solution, the method for preparing carboxylated graphite comprises the following steps: Mixing graphite and oxidizing acid solution to perform carboxylation reaction to obtain carboxylated graphite; After the carboxylation reaction, filtering, washing and drying are performed in sequence; The components of the oxidizing acid solution include hydrogen peroxide, permanganate, and concentrated sulfuric acid; The mass ratio of the hydrogen peroxide, permanganate and concentrated sulfuric acid is 1-5:5-10:100-200; The temperature of the carboxylation reaction is 50-80° C. and the time is 6-24 hours.
[0014] As a further technical solution, the conductive agent includes one or more of carbon nanotubes, graphene, carbon black, and carbon fibers; The coupling agent includes an aluminum-based coupling agent, and the aluminum-based coupling agent includes one or more of distearoyloxyisopropoxyaluminate, isopropyl distearoyloxyaluminate, trimethyl aluminate, and triisopropyl aluminate; The transition metal precursor includes a water-soluble salt containing a transition metal element, and the transition metal element includes one or more of iron, cobalt, and nickel; The carbon source includes a water-soluble resin; The water-soluble resin includes one or more of diallyl isophthalate resin, malic acid resin, acrylic resin, fumaric acid resin, and alkyd resin.
[0015] As a further technical solution, the temperature of the solvent thermal treatment is above 100°C, the time is 6-18h, and the pressure is 1-5MPa; preferably, the temperature of the solvent thermal treatment is 100-200°C; The temperatures of the first carbonization and the second carbonization are independently 1000-1400° C.; The holding time of the first carbonization and the second carbonization is independently 1 to 6 hours.
[0016] As a further technical solution, the in-situ growth of carbon nanotubes is carried out in an atmosphere containing a gaseous carbon source; The gaseous carbon source includes a gaseous carbon-containing raw material with a carbon number of less than 12. Preferably, the gaseous carbon source includes one or more of alkanes, alkenes, alkynes, and benzene with a carbon number of less than 8. The atmosphere containing the gaseous carbon source also includes hydrogen; the volume ratio of the gaseous carbon source to the hydrogen is 5 to 15:1; The flow rate of the atmosphere containing the gaseous carbon source is 10-50 sccm; The in-situ growth of carbon nanotubes is carried out at a temperature of 700-1000°C and a time of 60-600 minutes; After the in-situ growth of the carbon nanotubes, washing and drying are performed in sequence; The washing process includes acid washing and water washing in sequence.
[0017] The invention also proposes the application of the graphite composite material obtained by the preparation method in lithium ion batteries.
[0018] The working principle and beneficial effects of the present invention are: In the present invention, amino graphite and carboxylated graphite are solvent-thermally bonded with the assistance of a coupling agent, and then a first-stage carbonization treatment is performed to obtain modified graphite with special physical and chemical characteristics, and further used as a substrate, hard carbon doped with transition metal elements is compounded on the surface of the modified graphite, and a vapor deposition treatment is performed on the surface to induce in-situ growth of carbon nanotubes on the hard carbon surface to obtain a graphite composite material; carboxylated graphite and amino graphite are innovatively hydrothermally condensed and carbonized, so that the graphites are connected to each other through chemical bonds, thereby increasing the tap density and reducing the impedance, and improving the surface activity, thereby increasing the insertion and extraction rate of lithium ions during the charge and discharge process; in addition, the modified graphite is further used as a substrate, and hard carbon and carbon nanotubes are compounded in sequence, so that the performance of the material can be further synergistically strengthened, the electronic conductivity of the material can be increased, and the rate performance can be improved.
[0019] The preparation method of the graphite composite material of the present invention can regulate the physicochemical characteristics of the material, can improve the electronic conductivity of the graphite material, improve its ion transmission channel, improve its fast charging, stability and other properties, and significantly improve the kinetic properties of the graphite electrode material by grafting chemical groups on the surface of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0021] Figure 1 This is a SEM image of the graphite composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1 The method for preparing a graphite composite material comprises the following steps: S1. Preparation of amino graphite: 30 g of hexamethylenediamine was dispersed evenly in 500 g of N,N-dimethylformamide, 100 g of artificial graphite was added and continued to be dispersed evenly, reacted at a temperature of 80° C. for 3 h, filtered, and the filter residue was transferred to a tubular furnace, and ammonia gas was introduced at a temperature of 550° C. for 2 h to obtain amino graphite; S2. Preparation of carboxylated graphite: 3 g of hydrogen peroxide, 8 g of potassium permanganate, and 150 g of concentrated sulfuric acid were added to 100 g of artificial graphite and reacted at 60° C. for 12 h, filtered, washed with deionized water, and vacuum dried at 80° C. for 24 h to obtain carboxylated graphite; S3, adding 100g of amino graphite and 100g of carboxylated graphite to 1000g of deionized water to prepare a 20wt% solution, then adding 80g of 5wt% carbon nanotube conductive agent solution and 5g of distearyloxyisopropoxyaluminate to disperse evenly, and transferring to a high-pressure reactor, reacting at a temperature of 100°C and a pressure of 3MPa for 12h, filtering, taking the filter residue, vacuum drying at 80°C for 24h, and carbonizing at a temperature of 1200°C for 3h to obtain modified graphite; S4, dissolving 20g of diallyl isophthalate resin in 2000g of deionized water to prepare a 1wt% solution, adding 3g of cobalt chloride catalyst to disperse evenly, adding 100g of modified graphite to disperse evenly, spray drying, placing in a rotary kiln, and carbonizing at a temperature of 1200°C for 3h to obtain graphite@transition metal-doped hard carbon material; S5. Transfer the graphite@transition metal-doped hard carbon material to a rotary kiln, first introduce argon inert gas to exhaust the air in the pipe, and heat it to 800°C, then introduce acetylene / hydrogen mixed gas (the volume ratio of acetylene and hydrogen is 10:1) with a flow rate of 30 sccm and keep warm for 300 minutes, then cool it to room temperature, and use 0.1 mol / L hydrochloric acid for pickling, and wash with deionized water to obtain a graphite composite material.
[0024] Example 2 The method for preparing a graphite composite material comprises the following steps: S1. Preparation of amino graphite: 10 g of hexamethylenediamine was dispersed evenly in 500 g of N,N-dimethylformamide, 100 g of artificial graphite was added and continued to be dispersed evenly, reacted at a temperature of 50° C. for 6 h, filtered, and the filter residue was transferred to a tubular furnace, and ammonia gas was introduced at a temperature of 500° C. for 3 h to obtain amino graphite; S2. Preparation of carboxylated graphite: 1 g of hydrogen peroxide, 5 g of potassium permanganate, and 100 g of concentrated sulfuric acid were added to 100 g of artificial graphite and reacted at 50° C. for 24 h, filtered, washed with deionized water, and vacuum dried at 80° C. for 24 h to obtain carboxylated graphite; S3, 100g of amino graphite and 50g of carboxylated graphite were added to 1500g of deionized water to prepare a 10wt% solution, and then 50g of 5wt% graphene conductive agent solution and 1g of isopropyl distearoyloxyaluminate were added and dispersed evenly, and transferred to a high-pressure reactor, reacted at a temperature of 80°C and a pressure of 1MPa for 18h, filtered, and the filter residue was taken. After vacuum drying at 80°C for 24h, it was carbonized at a temperature of 1000°C for 6h to obtain modified graphite; S4, dissolving 10g of malic acid resin in 100g of deionized water to prepare a 1wt% solution, adding 1g of nickel chloride catalyst to disperse evenly, adding 100g of modified graphite to disperse evenly, spray drying, placing in a rotary kiln, and carbonizing at a temperature of 1000°C for 6h to obtain graphite@transition metal-doped hard carbon material; S5. Transfer the graphite@transition metal-doped hard carbon material to a rotary kiln, first introduce argon inert gas to exhaust the air in the pipe, and heat it to 700°C, then introduce acetylene / hydrogen mixed gas (the volume ratio of acetylene and hydrogen is 15:1) with a flow rate of 10sccm and keep warm for 600min, then cool it to room temperature, and use 0.1mol / L hydrochloric acid for pickling, and wash with deionized water to obtain a graphite composite material.
[0025] Example 3 The method for preparing a graphite composite material comprises the following steps: S1. Preparation of amino graphite: 50 g of hexamethylenediamine was dispersed evenly in 500 g of N,N-dimethylformamide, 100 g of artificial graphite was added and continued to be dispersed evenly, reacted at a temperature of 100° C. for 1 h, filtered, and the filter residue was transferred to a tubular furnace, and ammonia gas was introduced at a temperature of 600° C. for 1 h to obtain amino graphite; S2. Preparation of carboxylated graphite: 5 g of hydrogen peroxide, 10 g of potassium permanganate, and 200 g of concentrated sulfuric acid were added to 100 g of artificial graphite and reacted at 80° C. for 6 h, filtered, washed with deionized water, and vacuum dried at 80° C. for 24 h to obtain carboxylated graphite; S3, adding 100g of amino graphite and 150g of carboxylated graphite to 830g of deionized water to prepare a 30wt% solution, then adding 100g of 5wt% carbon black conductive agent solution and 10g of trimethyl aluminate to disperse evenly, and transferring to a high-pressure reactor, reacting at a temperature of 150°C and a pressure of 5MPa for 6h, filtering, taking the filter residue, vacuum drying at 80°C for 24h, and carbonizing at a temperature of 1400°C for 1h to obtain modified graphite; S4, dissolving 30g of fumaric acid resin in 3000g of deionized water to prepare a 1wt% solution, adding 5g of cobalt chloride catalyst to disperse evenly, adding 100g of modified graphite to disperse evenly, spray drying, placing in a rotary kiln, and carbonizing at a temperature of 1400°C for 1h to obtain graphite@transition metal-doped hard carbon material; S5. Transfer the graphite@transition metal-doped hard carbon material to a rotary kiln, first introduce argon inert gas to exhaust the air in the tube, and heat it to 1000°C, then introduce acetylene / hydrogen mixed gas (the volume ratio of acetylene and hydrogen is 5:1) at a flow rate of 50sccm for 60 minutes, then cool it to room temperature, and use 0.1mol / L hydrochloric acid for pickling, and then wash with deionized water to obtain a graphite composite material.
[0026] Comparative Example 1 The method for preparing a graphite composite material comprises the following steps: S1. Add 200 g of artificial graphite to 1000 g of deionized water to prepare a 20 wt% solution, then add 80 g of 5 wt% carbon nanotube conductive agent solution and disperse evenly, and transfer to a high-pressure reactor, react at a temperature of 100 ° C and a pressure of 3 MPa for 12 h, filter, take the filter residue, vacuum dry it at 80 ° C for 24 h, and carbonize it at a temperature of 1200 ° C for 3 h to obtain modified graphite; S2, dissolving 20g of diallyl isophthalate resin in 2000g of deionized water to prepare a 1wt% solution, adding 3g of cobalt chloride catalyst to disperse evenly, adding 100g of modified graphite to disperse evenly, spray drying, placing in a rotary kiln, and carbonizing at a temperature of 1200°C for 3h to obtain graphite@transition metal-doped hard carbon material; S3. Transfer the graphite@transition metal-doped hard carbon material to a rotary kiln, first introduce argon inert gas to exhaust the air in the pipe, and heat it to 800°C, then introduce acetylene / hydrogen mixed gas (the volume ratio of acetylene and hydrogen is 10:1) with a flow rate of 30sccm and keep warm for 300min, then cool it to room temperature, and use 0.1mol / L hydrochloric acid for pickling, and wash with deionized water to obtain a graphite composite material.
[0027] Comparative Example 2 The only difference between this comparative example and Example 1 is that no cobalt chloride catalyst is added in step S4.
[0028] Comparative Example 3 The difference between this comparative example and Example 1 is that step S1 is not included and 100 g of amino graphite in step S3 is replaced by 100 g of carboxylated graphite.
[0029] Comparative Example 4 The difference between this comparative example and Example 1 is that step S2 is not included and 100 g of carboxylated graphite in step S3 is replaced by 100 g of amino graphite.
[0030] Comparative Example 5 The only difference between this comparative example and Example 1 is that distearoyloxyisopropoxyaluminate is not added in step S3.
[0031] Comparative Example 6 The method for preparing a graphite composite material comprises the following steps: S1. Preparation of amino graphite: 30 g of hexamethylenediamine was dispersed evenly in 500 g of N,N-dimethylformamide, 100 g of artificial graphite was added and continued to be dispersed evenly, reacted at a temperature of 80° C. for 3 h, filtered, and the filter residue was transferred to a tubular furnace, and ammonia gas was introduced at a temperature of 550° C. for 2 h to obtain amino graphite; S2. Preparation of carboxylated graphite: 3 g of hydrogen peroxide, 8 g of potassium permanganate, and 150 g of concentrated sulfuric acid were added to 100 g of artificial graphite and reacted at 60° C. for 12 h, filtered, washed with deionized water, and vacuum dried at 80° C. for 24 h to obtain carboxylated graphite; S3, adding 100g of amino graphite and 100g of carboxylated graphite to 1000g of deionized water to prepare a 20wt% solution, then adding 80g of 5wt% carbon nanotube conductive agent solution and 5g of distearyloxyisopropoxyaluminate to disperse evenly, and transferring to a high-pressure reactor, reacting at a temperature of 100°C and a pressure of 3MPa for 12h, filtering, taking the filter residue, vacuum drying at 80°C for 24h, and carbonizing at a temperature of 1200°C for 3h to obtain modified graphite; S4. Dissolve 20 g of diallyl isophthalate resin in 2000 g of deionized water to prepare a 1 wt% solution, add 3 g of cobalt chloride catalyst and disperse it evenly, add 100 g of modified graphite and disperse it evenly, spray dry, place in a rotary kiln, and carbonize at a temperature of 1200 ° C for 3 hours to obtain a graphite composite material.
[0032] Comparative Example 7 The method for preparing a graphite composite material comprises the following steps: S1. Preparation of amino graphite: 30 g of hexamethylenediamine was dispersed evenly in 500 g of N,N-dimethylformamide, 100 g of artificial graphite was added and continued to be dispersed evenly, reacted at a temperature of 80° C. for 3 h, filtered, and the filter residue was transferred to a tubular furnace, and ammonia gas was introduced at a temperature of 550° C. for 2 h to obtain amino graphite; S2. Preparation of carboxylated graphite: 3 g of hydrogen peroxide, 8 g of potassium permanganate, and 150 g of concentrated sulfuric acid were added to 100 g of artificial graphite and reacted at 60° C. for 12 h, filtered, washed with deionized water, and vacuum dried at 80° C. for 24 h to obtain carboxylated graphite; S3, adding 100g of amino graphite and 100g of carboxylated graphite to 1000g of deionized water to prepare a 20wt% solution, then adding 80g of 5wt% carbon nanotube conductive agent solution and 5g of distearyloxyisopropoxyaluminate to disperse evenly, and transferring to a high-pressure reactor, reacting at a temperature of 100°C and a pressure of 3MPa for 12h, filtering, taking the filter residue, vacuum drying at 80°C for 24h, and carbonizing at a temperature of 1200°C for 3h to obtain modified graphite; S4. Transfer the modified graphite to a rotary kiln, first introduce argon inert gas to exhaust the air in the tube, and heat it to 800°C, then introduce acetylene / hydrogen mixed gas (the volume ratio of acetylene and hydrogen is 10:1) with a flow rate of 30 sccm and keep warm for 300 minutes, then cool it to room temperature, and use 0.1 mol / L hydrochloric acid for pickling, and wash with deionized water to obtain a graphite composite material.
[0033] The performance tests were performed on the graphite composite materials obtained in Examples 1 to 3 and Comparative Examples 1 to 7 respectively: 1. SEM test The graphite composite material prepared in Example 1 was subjected to SEM test, and the test results are as follows: Figure 1 As shown. Figure 1 It can be seen that the graphite composite material prepared in Example 1 is in granular form with uniform size distribution, and its particle size is between 10 and 15 μm.
[0034] 2. Physical and chemical performance test The graphite composite materials prepared in each embodiment and each comparative example were tested for powder conductivity, powder compaction density, specific surface area and powder OI value.
[0035] Test of powder conductivity: The composite materials prepared in each case were pressed into block structures, and then the conductivity of the powder was tested using a four-probe tester.
[0036] Test of powder compaction density: Weigh the graphite composite powders prepared in the embodiment and the comparative example respectively and place them in a mold, and press them with a pressure of 2T (using a powder compaction density meter, place 1g of powder in a fixed kettle and then press it with a pressure of 2T, let it stand for 10S, then calculate the volume under pressing, and calculate the compaction density), and calculate the powder compaction density.
[0037] Specific surface area test: tested according to the national standard GB / T 24533-2019 "Graphite Anode Materials for Lithium-ion Batteries".
[0038] Powder OI value: tested by XRD.
[0039] The results are shown in Table 1.
[0040] Table 1 Physical and chemical properties test results
[0041] 3. Button battery test The graphite composite materials prepared in Examples 1-3 and Comparative Examples 1-7 are used as negative electrode materials for lithium-ion batteries and assembled into button cells. The specific preparation method of the negative electrode material is: adding a binder, a conductive agent and a solvent to the graphite composite material, stirring and slurrying, coating on a copper foil, drying and rolling. The binder used is LA132 binder, the conductive agent is SP, and the solvent is double distilled water. According to the composite material: SP: LA132: double distilled water = 95g: 1g: 4g: 220mL, a negative electrode sheet is prepared; a metal lithium sheet is used as a counter electrode; the electrolyte uses LiPF6 / EC+DEC, in which LiPF6 is the electrolyte, a mixture of EC and DEC with a volume ratio of 1:1 is the solvent, and the electrolyte concentration is 1.2mol / L; the diaphragm uses polyethylene (PE), polypropylene (PP) or polyethylene propylene (PEP) composite film. The button cell is assembled in an argon-filled glove box. The electrochemical performance was tested on a Wuhan Blue Electric CT2001A battery tester, with a charge and discharge voltage range of 0.005V to 2.0V and a charge and discharge rate of 0.1C, to test the first discharge capacity and first efficiency of the button cell and its rate performance (1C / 0.1C). The test results are shown in Table 2.
[0042] Table 2 Button battery test
[0043] It can be seen from Table 2 that the lithium ion batteries using the graphite composite materials obtained in Examples 1-3 as negative electrode materials have better first discharge specific capacity and rate performance than those in Comparative Examples 1-7.
[0044] Compared with Comparative Examples 3 to 4, the lithium-ion battery using the graphite composite material as the negative electrode material prepared in Example 1 has better first discharge specific capacity and rate performance, indicating that the lithium-ion battery using the graphite composite material prepared by jointly using amino graphite and carboxyl graphite as the negative electrode material has better kinetic performance.
[0045] Compared with Comparative Examples 6-7, the lithium-ion battery using the graphite composite material as the negative electrode material prepared in Example 1 has better first discharge specific capacity and rate performance, indicating that the graphite composite material uses graphite as the core to sequentially prepare transition metal-doped hard carbon and in-situ grown carbon nanotubes on the surface, and the kinetic performance of the lithium-ion battery after being used as the negative electrode material is better.
[0046] 4. Soft pack battery test The graphite composite material was slurried and coated to prepare the negative electrode sheet (preparation method is the same as above), lithium iron phosphate was used as the positive electrode (the positive electrode material includes lithium iron phosphate PVDF and conductive carbon black with a weight ratio of 9:0.5:0.5), LiPF6 (solvent is EC+DEC, volume ratio is 1:1, electrolyte concentration is 1.3 mol / L) was used as the electrolyte, and Celgard2400 membrane was used as the separator to prepare a 5Ah soft pack battery, and the cycle performance and rate performance of the soft pack battery were tested. The rate performance test conditions are as follows: charging DCR according to different charging SOC (90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, 10%, 5%). The test results are shown in Table 3.
[0047] Table 3 Soft pack battery test
[0048] It can be seen from Table 3 that, compared with Comparative Examples 1 to 7, the soft-pack batteries prepared from the graphite composite materials prepared in Examples 1 to 3 of the present invention have lower DCR.
[0049] Compared with Comparative Examples 3 to 4, the DCR of the soft-pack battery using the graphite composite material as the negative electrode material prepared in Example 1 is lower at different SOCs, indicating that the lithium-ion battery using the graphite composite material prepared by jointly using amino graphite and carboxyl graphite as the negative electrode material has better kinetic performance.
[0050] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a graphite composite material, characterized in that: The following steps are involved: S1, mixing amino graphite, carboxyl graphite, conductive agent, coupling agent and solvent, performing solvent thermal treatment, taking filter residue, drying and carbonizing for the first time to obtain modified graphite; S2, mixing the modified graphite, transition metal precursor and carbon source, drying and carbonizing for a second time to obtain graphite@transition metal doped hard carbon material; S3, in-situ growing carbon nanotubes on the surface of the graphite@transition metal-doped hard carbon material to obtain a graphite composite material.
2. The method for preparing the graphite composite material according to claim 1, characterized in that: The mass ratio of the amino graphite, the carboxyl graphite, the conductive agent and the coupling agent is 100:50-150:1-5:1-10.
3. The method for preparing the graphite composite material according to claim 1, characterized in that: The mass ratio of the total mass of the amino graphite and the carboxylated graphite to the solvent is 1-3:
10.
4. The method for preparing the graphite composite material according to claim 1, characterized in that: The mass ratio of the carbon source, the transition metal precursor and the modified graphite is 10-30:1-5:
100.
5. The method for preparing the graphite composite material according to claim 1, characterized in that: The preparation method of the amino graphite comprises the following steps: Amine compounds and graphite are used as raw materials for mixed reaction, and the filter residue is subjected to ammoniation and roasting to obtain amino graphite; The amine compound includes a diamine or a polyamine compound, and preferably, the amine compound includes a C2-C8 diamine compound; The mass ratio of the amine compound to graphite is 10-50:100; The mixing reaction time is 1-6 hours and the temperature is 50-100°C; The time of the ammoniation calcination is 1 to 3 hours.
6. The method for preparing the graphite composite material according to claim 1, characterized in that: The preparation method of the carboxylated graphite comprises the following steps: Mixing graphite and oxidizing acid solution to perform carboxylation reaction to obtain carboxylated graphite; The components of the oxidizing acid solution include hydrogen peroxide, permanganate, and concentrated sulfuric acid; The mass ratio of the hydrogen peroxide, permanganate and concentrated sulfuric acid is 1-5:5-10:100-200; The temperature of the carboxylation reaction is 50-80° C. and the time is 6-24 hours.
7. The method for preparing a graphite composite material according to claim 1, characterized in that: The conductive agent includes one or more of carbon nanotubes, graphene, carbon black, and carbon fibers; The coupling agent includes an aluminum-based coupling agent, and the aluminum-based coupling agent includes one or more of distearoyloxyisopropoxyaluminate, isopropyl distearoyloxyaluminate, trimethyl aluminate, and triisopropyl aluminate; The transition metal precursor includes a water-soluble salt containing a transition metal element, and the transition metal element includes one or more of iron, cobalt, and nickel; The carbon source includes a water-soluble resin; The water-soluble resin includes one or more of diallyl isophthalate resin, malic acid resin, acrylic resin, fumaric acid resin, and alkyd resin.
8. The method for preparing the graphite composite material according to claim 1, characterized in that: The temperature of the solvent thermal treatment is above 100°C, the time is 6-18h, and the pressure is 1-5MPa; preferably, the temperature of the solvent thermal treatment is 100-200°C; The temperatures of the first carbonization and the second carbonization are independently 1000-1400° C.; The holding time of the first carbonization and the second carbonization is independently 1 to 6 hours.
9. The method for preparing the graphite composite material according to claim 1, characterized in that: The in-situ growth of carbon nanotubes is carried out in an atmosphere containing a gaseous carbon source; The gaseous carbon source includes a gaseous carbon-containing raw material with a carbon number of less than 12. Preferably, the gaseous carbon source includes one or more of alkanes, alkenes, alkynes, and benzene with a carbon number of less than 8. The atmosphere containing the gaseous carbon source also includes hydrogen; the volume ratio of the gaseous carbon source to the hydrogen is 5 to 15:1; The flow rate of the atmosphere containing the gaseous carbon source is 10-50 sccm; The temperature of the in-situ growth of carbon nanotubes is 700-1000° C. and the time is 60-600 min.
10. Use of the graphite composite material obtained according to the preparation method according to any one of claims 1 to 9 in lithium ion batteries.
Citation Information
Patent Citations
Quick-charging lithium battery
CN114361410A
Multi-element carbon-based fast-charging negative electrode composite material and preparation method thereof
CN114447305A
Composite material, electrode, method to produce the material and the electrode and electrochemical cell comprising the electrode
CN108292744A
Hard carbon negative electrode material with low-voltage platform as well as preparation method and application of hard carbon negative electrode material
CN117239121A
High-energy-density fast-charging graphite composite material and preparation method thereof
CN118993057A